SPECIFICS OF SANITARY CONTROL OF VEGETABLE PRODUCTION AND SOIL DURING USE OF MIXTURES PESTICIDES - Moskalenko, V.F.; Пельо, І.М.; Sasinovych, L.M. (World of Medicine and Biology, 2014)
The parameters of the degradation of pesticide active ingredients that make up the mix. Comparative analysis of the components within each of 15 pesticide compounds studied by us set the parameters of their degradation (τ50, τ95, τ99 and k degradation) in vegetables and soil, as well as other safety characteristics based on the proportion of drugs in the mixture, and the content of active substances in preparations allowed us to identify the limiting component of each mix, which is recommended to carry out sanitary control of soil and vegetables in their application. The results of the experiment to study the dynamics of the content of active ingredients of drugs that are part of the mix in vegetables and soil showed that regardless of the norms of consumption, frequency and method of treatment, the nature of the studied crops (cucumbers, tomatoes, peppers, potatoes, onions, peas vegetable, cabbage, eggplant, beets, carrots, coriander), type of soil and agro-climatic zones, statistically significant differences in the behavior of these substances was not. The remaining amount of the active substances in vegetables during harvest in no case exceed the hygienic standards. Organoleptic properties of samples of vegetables sampled during the harvesting of test sites were comparable to control samples vegetables.